Freedom and the conditions of will: Between philosophy and neuroscience - Bremer, Józef (Journal of Public Governance, 2014)
Beginning with the notion of “volitional act”, the Author describes Benjamin Libet’s experiment concerning time relations between taking a conscious, volitional decision and acting on it, and the measurement of readiness potential in the brain. Next, the Author discusses and analyzes two groups of neuroscientific interpretations of the experiment in order to arrive at a scientific explanation of the nature of free will. According to these interpretations, free will is defi ned either as (1) an emergent quality that influences its neuronal basis (Benjamin Libet, Roger Sperry), or (2) an epiphenomenal entity, fictional, unlike causally determined neuronal processes (Gerhard Roth, Wolf Singer). The Author attempts to demonstrate that, based on research in contemporary neuroscience, it is impossible to definitively state that what is commonly referred to as free will is fi ction. If we assume the traditional definition of free will, it can be understood as an emergent quality.